Communicating Crimes: Covering Gangs in Contemporary Canadian Journalism - Richardson, Chris (2012)
In this integrated-article dissertation, I examine representations of gangs in Canadian journalism, focusing primarily on contemporary newspaper reporting. While the term “gang” often refers to violent groups of young urban males, it can also signify outlaw bikers, organized crime, terrorist cells, non-criminal social groups, and a wide array of other collectives. I build on Pierre Bourdieu’s theoretical framework to probe this ambiguity, seeking to provide context and critical assessments that will improve crime reporting and its reception. In the course of my work, I examine how popular films like West Side Story inform journalists’ descriptions of gangs. Though reporters have been covering suburban gangs for decades, they continue to place gangs in the “inner city,” which fits better with imagery from the Manhattan musical. Meanwhile, politicians and political commentators frequently exploit the ambiguity of gangs, applying its rhetoric to opponents and evoking criminal connotations in mediated debates. Based on these findings, I argue that Bourdieu’s concept of symbolic violence envelopes contemporary Canadian newspapers and I suggest that journalists must incorporate alternative images and discourses to challenge these problematic communication practices. Consequently, my last chapter explores art projects in Regent Park and Clichy-sous-Bois, where I find techniques that challenge the dominant tropes of gangs within the news media and provoke more nuanced conversations about such groups. I conclude by outlining the implications of my research for journalists, gang scholars, and concerned citizens